Strategi Manajemen Inovasi Dalam Mempertahankan Daya Saing Di Pasar Global - Adina khasanah; Nasya Anisyah Lerian; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Innovation management has become a key factor in increasing competitiveness in the increasingly dynamic and competitive global market. Innovation includes not only the development of new products, but also process improvements, marketing strategies, and business models to meet the needs of the ever-evolving market. In a global context, companies are required to adapt to the latest technologies, consumer trends, and changes in international regulations. This paper discusses how the implementation of innovation management can be an effective strategy to increase the competitiveness of companies in the global market. By utilizing digital technology, cross-cultural collaboration, and data-driven approaches, companies are able to create sustainable added value. Case studies from various industries show that organizations that integrate innovation into their vision and operations tend to have a more significant competitive advantage. The results of the study emphasize the importance of investing in research and development (R&D), empowering human resources, and strategic partnerships to support the innovation process. This abstract concludes that effective innovation management not only drives company growth but also plays a vital role in creating a sustainable business ecosystem in the global market. Thus, innovation management is key for companies to remain relevant and competitive in the ever-changing global competition.